PENGARUH WEB MODUL IPA TERINTEGRASI POTENSI LOKAL “EKOSISTEM PEGUNUNGAN DIENG” TERHADAP THINKING SKILL - Ray Cinthya Habellia; Suyanta Suyanta (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
THE EFFECT OF SCIENCE WEB MODUL INTEGRATED LOCAL POTENTIAL OF DIENG MOUNTAIN ECOSYSTEM TOWARD THINGKING SKILL Abstract21st-century learning requires learning media that can improve thinking skills, including understanding information, formulating alternative solutions and solving problems in the environment around students by utilizing the available information sources. This study aimed to identify the influence of the science web module integrated local potential